2017
DOI: 10.1039/c7ra06111k
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous selective reduction of PHB as a useful method for preparation of oligodiols and surface modification

Abstract: A selective heterogeneous reduction of natural PHB with lithium borohydride as a reducing agent has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…The structural characterization of the oligomers conducted using NMR and ESI-MS n analyses confirmed that oligomers were terminated by two hydroxyl end groups. The reduction of the PHA occurred in a statistical way, regardless of the chemical structure of the comonomer units or of the microstructure of the polyester chain [71,72]. This method can be used to synthesize various PHA oligodiols that were useful in the further synthesis of tailor-made biodegradable materials [73,74].…”
Section: Functionalization Of Pha To Oligomers Containing Hydroxyl End Groupsmentioning
confidence: 99%
“…The structural characterization of the oligomers conducted using NMR and ESI-MS n analyses confirmed that oligomers were terminated by two hydroxyl end groups. The reduction of the PHA occurred in a statistical way, regardless of the chemical structure of the comonomer units or of the microstructure of the polyester chain [71,72]. This method can be used to synthesize various PHA oligodiols that were useful in the further synthesis of tailor-made biodegradable materials [73,74].…”
Section: Functionalization Of Pha To Oligomers Containing Hydroxyl End Groupsmentioning
confidence: 99%
“…The observed decrease in the PHA’s M w impairs the utilization of the biopolymer in most of the conventional applications of plastics due to the loss of mechanical properties. Nevertheless, there are specific applications for which low-M w PHAs are of interest, such as their utilization as plasticizers [ 44 ] and surfactants, or for the preparation of graft and block co-polymers, which are useful for the fabrication of bio-adhesives, drug-delivery systems, drug-coating systems, and tissue-engineering materials [ 45 , 46 , 47 ]. Nevertheless, for biomedical and pharmaceutical uses, the biopolymers would require further purification to meet the requirements of such high-value areas.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, for biomedical and pharmaceutical uses, the biopolymers would require further purification to meet the requirements of such high-value areas. For such applications, the PHA molecules are depolymerized into monomers or short oligomers (10 2 –10 4 g/mol) by physical (e.g., thermal decomposition), chemical methods (e.g., acid hydrolysis, alcoholysis), and/or enzymatic methods [ 46 , 47 , 48 ]. The developed SBW–hypochlorite digestion methodology could be of great value for the extraction of the biopolymer with the appropriate M w for use in such areas of application, without the need to resort to the chemical hydrolysis of high-M w PHA.…”
Section: Resultsmentioning
confidence: 99%
“…The higher density of these groups was attained by using lithium borohydride (LiBH 4 ). In our previous study, this reducing agent permitted us to obtain low-molar-mass poly(3-hydroxybutyrate) (PHB) with hydroxyl terminal groups, which was confirmed by GPC, proton NMR, and ESI-MS experiments [ 53 ]. The oligomers, of course, were synthesized in a heterogeneous system, that is, by reducing high-molar-mass PHB in the form of a powder.…”
Section: Introductionmentioning
confidence: 95%